From gobbledygook to clearly written annual IEP goals - Bateman, Barbara (USA : Attainment Company, Inc., 2007)
Writing clear, measurable annual IEP goals is a difficult skill to master. The good news is that goal writing is easy once the steps are revealed. In her latest book, Dr Barbara Bateman takes poorly written goals and rewrites them into clear, concise goals. You learn to simplify the process by focusing on four ideas: observable behaviour, measurable criteria, a given or condition for success, and a final test
Keywords: Individualized education programs; Children with disabilities. -- Education